An mpeg-oh modified polyether block polyamide gas separation composite membrane and a preparation method thereof

CN122625065BActive Publication Date: 2026-10-13SUZHOU LABORATORY +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611124119.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-13
Estimated Expiration
2046-07-28

AI Technical Summary

Technical Problem

然而,该类材料仍存在一定局限

Benefits of technology

首先,本发明巧妙且精准地利用了聚醚嵌段聚酰胺(Pebax)极其有限的分子链端羟基,在羰基二咪唑(CDI)的介导下,使Pebax端羟基与mPEG-OH发生共价偶联(形成高度稳定的碳酸酯键连接)。这种改性是严格发生在长链两端的“线性嵌段延伸”,不仅从根本上杜绝了游离mPEG在长期运行中的流失和相分离问题,而且完全保留了Pebax极其优异的本征成膜性,使其能够直接作为选择性分离层的成膜主体材料。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122625065B_ABST
    Figure CN122625065B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of gas separation membrane materials, and particularly relates to an mPEG-OH modified polyether block polyamide gas separation composite membrane and a preparation method thereof, and application of the mPEG-OH modified polyether block polyamide gas separation composite membrane in mixed gas separation. The application provides an mPEG-OH modified polyether block polyamide gas separation composite membrane and a preparation method thereof. N,N'-carbonyl diimidazole (CDI) is used to activate end groups of polyether block polyamide molecular chains, and mPEG-OH is introduced to perform end group polyether modification. On the basis of maintaining a polyether block polyamide main structure, the method can improve polyether chain segment characteristics in the material, and has an influence on chain segment packing modes and crystallization behaviors, so as to improve casting solution uniformity, membrane layer film forming quality and structure stability, and be beneficial to improving carbon dioxide separation performance of a thin film composite membrane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of gas separation membrane material technology, specifically relating to an mPEG-OH modified polyether block polyamide gas separation composite membrane and its preparation method, as well as its application in mixed gas separation. Background Technology

[0002] Carbon dioxide separation has significant applications in post-combustion carbon capture, natural gas purification, and industrial waste gas treatment. Compared to traditional methods such as absorption, adsorption, and cryogenic separation, membrane separation technology offers advantages such as continuous processes, lower energy consumption, compact equipment, and ease of modular scaling, thus being considered one of the most promising gas separation technologies. Among existing membrane materials, polymer membranes have attracted widespread attention due to their mature manufacturing processes and relatively low cost; however, a balance between gas transport performance, membrane stability, and processing adaptability is often difficult to achieve, limiting their further application.

[0003] Polyether-block polyamide materials combine the strong affinity of polyether segments for carbon dioxide with the mechanical support provided by polyamide segments, making them a commonly used polymer membrane material in gas separation. Pebax, a representative polyether-block polyamide, exhibits good overall performance in carbon dioxide separation due to the simultaneous presence of flexible and rigid polyether segments. However, this type of material still has certain limitations. On the one hand, the molecular chain stacking and crystallization behavior of Pebax significantly affects the gas transport process; overly dense segment stacking is detrimental to carbon dioxide diffusion. On the other hand, existing modification methods mostly focus on blending, crosslinking, or introducing external functional components, often involving numerous process steps, complex implementation conditions, or significant impacts on the main structure, hindering the unification of material structure control with the actual membrane fabrication process.

[0004] For thin-film composite membranes, the selective separation layer is relatively thin, and the state of polymer molecular chains, the uniformity of the casting solution, and the interfacial film-forming behavior are more likely to affect the continuity and structural integrity of the membrane. Therefore, if the molecular chain ends can be controlled in a simple and feasible way while maintaining the Pebax bulk block structure, so that the material can moderately affect the chain segment stacking and crystallization behavior without destroying the bulk structure, it is expected to improve the film-forming uniformity of the selective separation layer and further enhance the carbon dioxide separation performance of the thin-film composite membrane.

[0005] mPEG-OH, containing polyether segments and terminal hydroxyl groups, can be introduced into polyether block polyamide systems as a functional polyether fragment. If mPEG-OH is introduced into the ends of Pebax molecular chains through a suitable activation method to achieve end-group polyetherification modification, it is expected that the polyether segment characteristics in the material can be improved while maintaining the main block structure of Pebax, and their segment stacking and crystallization behavior can be controlled, thereby improving the film formation quality and gas separation performance. Therefore, developing an end-group polyetherified modified polyether block polyamide thin film composite membrane and its preparation method that is simple to prepare, easy to implement, and can achieve structural control effects is of practical significance. Summary of the Invention

[0006] To address the aforementioned problems, this invention provides an mPEG-OH modified polyether block polyamide gas separation composite membrane and its preparation method. The method involves activating the terminal groups of the polyether block polyamide molecular chains with carbonyl diimidazole (CDI) and introducing polyethylene glycol monomethyl ether (mPEG-OH) for end-group polyetherification modification. While maintaining the main structure of the polyether block polyamide, this method enhances the polyether segment characteristics in the material and influences its segment stacking mode and crystallization behavior, thereby improving the uniformity of the casting solution, the membrane formation quality, and structural stability, and ultimately improving the carbon dioxide separation performance of the thin-film composite membrane.

[0007] First, the present invention provides an end-group modified polyether block polyamide composite membrane, comprising a base membrane and a selective separation layer disposed above the base membrane; the selective separation layer is formed of mPEG-OH modified polyether block polyamide; the mPEG-OH modified polyether block polyamide utilizes carbonyl diimidazole as a coupling agent to activate the terminal hydroxyl groups of the polyether block polyamide, and then covalently couples it with the terminal hydroxyl groups of mPEG-OH to form a modified polymer with an extended main chain structure.

[0008] Preferably, the base film is a porous support layer or a porous support layer containing an intermediate layer; the intermediate layer is a polydimethylsiloxane layer.

[0009] Preferably, the porous support layer is one of polysulfone, polyethersulfone, polyacrylonitrile, polyvinylidene fluoride, polytetrafluoroethylene, polypropylene, polyethylene, polyimide, polyetherimide, or polyphenylene sulfide.

[0010] Preferably, the flexible segment of the polyether block polyamide is polyethylene oxide; and / or, the polyether block polyamide is polyether block polyamide (Pebax) 1657.

[0011] Preferably, the weight-average molecular weight of the mPEG-OH is 500 to 10,000 Daltons, and more preferably, the weight-average molecular weight is 500 to 2,000 Daltons.

[0012] Secondly, the present invention provides a method for preparing the above-mentioned composite membrane, which includes the following steps: Step 1: Dissolve the polyether block polyamide in a mixed solvent and stir under heating until dissolved to obtain a polymer solution; Step 2: Add carbonyl diimidazole to the polymer solution obtained in Step 1 to activate the terminal groups of the polyether block polyamide molecular chain. Step 3: Add mPEG-OH to the system obtained in Step 2 and continue the reaction to obtain mPEG-OH modified polyether block polyamide; Step four: The product obtained in step three is prepared into a casting solution, and the casting solution is coated on the surface of the base film. After drying, a selective separation layer is formed, thereby obtaining the composite film.

[0013] Preferably, in step one, the mixed solvent is a mixture of ethanol and water, with a mass ratio of ethanol to water of 10-90:90-10, more preferably, the mass ratio is 60-80:20-40; and / or, in step one, the heating condition is stirring at 40-120°C, more preferably, the heating condition is 60-90°C.

[0014] Preferably, in step two, the reaction temperature is 10-100℃ and the reaction time is 0.1-10 hours; more preferably, the reaction temperature is 20-50℃ and the reaction time is 1-4 hours; and / or, in step three, the reaction temperature is 20-80℃ and the reaction time is 0.1-10 hours; more preferably, the reaction temperature is 20-50℃ and the reaction time is 2-6 hours.

[0015] Preferably, the mass ratio of the polyether block polyamide, carbonyl diimidazole and mPEG-OH is 100:5-80:5-80, more preferably, the mass ratio is 100:15-75:10-50.

[0016] Preferably, after step three, a purification step is also included: the reaction solution is poured into excess n-hexane for precipitation, and the precipitated product is separated and / or washed, and then vacuum dried at 30-100℃ (more preferably, the temperature is 60-90℃) for 1-100 hours (more preferably, the drying time is 10-24 hours) to constant weight to obtain purified mPEG-OH modified polyether block polyamide.

[0017] Preferably, in step four, the coating is applied using a blade coating method and / or a spin coating method.

[0018] Finally, the present invention also provides an application of the above-mentioned composite membrane in the field of mixed gas separation, wherein the mixed gas includes carbon dioxide and at least one of the group consisting of nitrogen, methane, hydrogen and carbon monoxide, wherein carbon dioxide permeates through the composite membrane.

[0019] Compared with the prior art, the present invention has the following beneficial effects: First, this invention ingeniously and precisely utilizes the extremely limited number of terminal hydroxyl groups in the polyether block polyamide (Pebax) molecular chain. Under the mediation of carbonyl diimidazole (CDI), the terminal hydroxyl groups of Pebax undergo covalent coupling with mPEG-OH (forming highly stable carbonate bonds). This modification is a strictly linear block extension occurring at both ends of the long chain, which not only fundamentally eliminates the loss and phase separation problems of free mPEG during long-term operation, but also completely preserves the excellent intrinsic film-forming properties of Pebax, enabling it to be directly used as the host material for the selective separation layer.

[0020] Secondly, this invention achieves precise control over the microscopic aggregation state and free volume of the polymer, breaking through the bottleneck of gas transport resistance. The tight packing and crystallization behavior of rigid polyamide segments in Pebax traditionally hinders rapid gas diffusion. This invention, without disrupting the original "alternating hard and soft segments" microphase separation structure of the Pebax main chain, effectively increases the characteristic proportion of flexible polyether segments in the material by introducing mPEG end groups. XRD results confirm that after covalent modification of the end groups, the shape and intensity of Pebax's characteristic diffraction peaks changed significantly. This indicates that the mPEG attached to the ends of the molecular chains acts like an "intramolecular plasticizer," moderately breaking the overly tight segment packing, expanding the free volume within the polymer, and thus opening a smoother transport channel for the rapid dissolution and diffusion of carbon dioxide molecules.

[0021] Finally, the thin-film composite membrane prepared by this invention achieves a simultaneous leap in CO2 separation flux, selectivity, and long-term stability. Thanks to the dual optimization of the aforementioned chemical structure and microscopic physical stacking, the casting solution of this invention exhibits excellent uniformity, forming an ultra-thin and defect-free continuous selective separation layer after coating onto the porous support layer (base membrane). Compared with unmodified traditional Pebax thin-film composite membranes or traditional "Pebax / mPEG physical blend membranes," the end-group modified composite membrane of this invention significantly increases carbon dioxide permeation flux while maintaining high CO2 / N2 selectivity. More importantly, because mPEG is firmly anchored to the polymer backbone by chemical bonds, this composite membrane exhibits excellent structural stability and anti-attenuation performance in long-term continuous gas separation operations, demonstrating high commercial conversion value in practical applications such as carbon capture and industrial exhaust gas treatment. Attached Figure Description

[0022] Figure 1 The proton NMR spectra of Pebax1657 (a), mPEG-OH (b), and mPEG-modified Pebax1657 (c) prepared in Example 1; Figure 2Fourier transform infrared spectra of Pebax1657 polymer, the mPEG-OH-10% modified Pebax polymer in Example 1, the mPEG-OH-20% modified Pebax polymer in Example 2, and the mPEG-OH-30% modified Pebax polymer in Example 3; Figure 3 X-ray diffraction patterns of Pebax1657 polymer, mPEG-OH-10% modified Pebax polymer in Example 1, mPEG-OH-20% modified Pebax polymer in Example 2, and mPEG-OH-30% modified Pebax polymer in Example 3; Figure 4 SEM images of the surface (a) and cross-section (b) of the Pebax 1657 thin film composite membrane prepared for Comparative Example 1, and SEM images of the surface (c) and cross-section (d) of the mPEG-OH-10% modified Pebax thin film composite membrane prepared for Example 4. Detailed Implementation

[0023] The embodiments of the present invention are described in detail below. These embodiments are exemplary and intended to explain the present invention, and should not be construed as limiting the invention. Unless otherwise specified, the raw materials used in the embodiments are all commercially available products, and the methods used are conventional methods in the art. Specifically, Pebax 1657 is a commercially available polyether block polyamide polymer purchased directly, and polyethylene glycol monomethyl ether (mPEG-OH) was purchased from Adamas, CAS number 9004-74-4, catalog number 01123311, reagent grade RG, with an average molecular weight of approximately 550 g / mol and a purity of 98%.

[0024] Example 1 This example describes the synthesis of mPEG-OH-10% modified Pebax1657 polymer. The specific steps are as follows: Pebax1657 (0.9 g) was added to a 70 / 30 wt% ethanol / water mixture (29.1 g) and magnetically stirred at 80 °C until completely dissolved to obtain a homogeneous polymer solution. Then, carbonyl diimidazole (CDI, 0.09 g) was added to the system, and the reaction was continued at 30 °C for 2 h to activate the terminal hydroxyl groups of the polyether block polyamide 1657 molecular chain. Next, methoxy polyethylene glycol (mPEG-OH) was added, accounting for 10% (0.09 g) of the Pebax1657 mass, and the reaction was continued at 30 °C for 3 h. After the reaction was complete, the reaction solution was slowly poured into excess n-hexane for precipitation. The precipitated polymer was separated by filtration and washed several times with n-hexane to remove unreacted small molecules and residual impurities. Finally, the obtained product was placed in a vacuum drying oven and dried at 80 °C for 12 h to constant weight to obtain mPEG-OH-10% modified Pebax1657 polymer.

[0025] Example 2 This example is used to synthesize mPEG-OH-20% modified Pebax1657 polymer. The only difference from Example 1 is that the amount of mPEG-OH added accounts for 20% of the mass of Pebax1657. The remaining steps are the same as in Example 1.

[0026] Example 3 This example is used to synthesize mPEG-OH-30% modified Pebax1657 polymer. The only difference from Example 1 is that the amount of mPEG-OH added accounts for 30% of the mass of Pebax1657. The remaining steps are the same as in Example 1.

[0027] Example 4 This embodiment is used to prepare a mPEG-OH-10% modified Pebax1657 thin film composite membrane. The mPEG-OH-10% modified Pebax1657 polymer obtained in Example 1 was dissolved in 10.000 g of an ethanol / water mixed solvent, wherein the mass ratio of ethanol to water was 70:30, to prepare a homogeneous casting solution with a concentration of 0.3%. A polysulfone porous support membrane with a PDMS interlayer was used as the base membrane. The casting solution was uniformly coated onto the surface of the base membrane using a doctor blade with a gap of 0.15 mm. The membrane was then dried in an oven at 50 °C for 6 h to obtain the mPEG-OH-10% modified Pebax1657 thin film composite membrane.

[0028] Example 5 This embodiment is used to prepare an mPEG-OH-20% modified Pebax1657 thin film composite membrane. The only difference from Example 4 is that the polymer component used to prepare the thin film composite membrane is replaced by the mPEG-OH-10% modified Pebax1657 polymer obtained in Example 1 with the mPEG-OH-20% modified Pebax1657 polymer obtained in Example 2. The remaining steps are the same as in Example 4.

[0029] Example 6 This embodiment is used to prepare an mPEG-OH-30% modified Pebax1657 thin film composite membrane. The only difference from Example 4 is that the polymer component used to prepare the thin film composite membrane is replaced by the mPEG-OH-10% modified Pebax1657 polymer obtained in Example 1 with the mPEG-OH-30% modified Pebax1657 polymer obtained in Example 3. The remaining steps are the same as in Example 4.

[0030] Comparative Example 1 This comparative example was used to prepare a Pebax1657 thin film composite membrane. The only difference from Example 4 was that the polymer component used to prepare the casting solution was replaced with Pebax1657 instead of the mPEG-OH-10% modified Pebax1657 polymer obtained in Example 1, and mPEG-OH and CDI were not added. The remaining steps were the same as in Example 4, and a Pebax1657 thin film composite membrane was obtained.

[0031] Comparative Example 2 This comparative example was used to prepare an mPEG-OH / Pebax1657 thin film composite membrane. The only difference from Example 4 is that, in preparing the casting solution, CDI activation and mPEG-OH end-group modification reactions were omitted. Instead, mPEG-OH and Pebax1657 were directly mixed. The remaining steps were the same as in Example 4. Specifically, mPEG-OH and Pebax1657 were dissolved in 10.000 g of an ethanol / water mixed solvent, wherein the mass ratio of ethanol to water was 70:30, and stirred to form a homogeneous casting solution. A polysulfone porous support membrane with a PDMS interlayer was used as the base membrane. The casting solution was uniformly coated onto the surface of the base membrane using a doctor blade with a gap of 0.15 mm. The membrane was then dried in a 50 ℃ oven for 6 h to obtain the mPEG-OH / Pebax1657 thin film composite membrane.

[0032] Comparative Example 3 This comparative example was used to prepare a CDI / Pebax1657 thin-film composite membrane. The only difference from Example 4 is that, in preparing the casting solution, mPEG-OH was not added; instead, Pebax1657 and CDI were directly mixed. The remaining steps were the same as in Example 4. Specifically, Pebax1657 was dissolved in 10,000 g of an ethanol / water mixed solvent, wherein the mass ratio of ethanol to water was 70:30. CDI was then added to the system, and the mixture was stirred to form a homogeneous casting solution. A polysulfone porous support membrane with a PDMS interlayer was used as the base membrane. The casting solution was uniformly coated onto the surface of the base membrane using a doctor blade with a gap of 0.15 mm. The membrane was then dried in a 50 °C oven for 6 h to obtain the CDI / Pebax1657 thin-film composite membrane.

[0033] Test Example 1: Characterization by Proton Nuclear Magnetic Resonance Spectroscopy The proton NMR spectra of commercially purchased Pebax1657, mPEG-OH, and mPEG-modified Pebax1657 prepared in Example 1 and subjected to hexane precipitation, repeated washing, and vacuum drying were analyzed. DMSO-d6 was used as the deuterated solvent in the tests, and the results are as follows: Figure 1 As shown.

[0034] The 1H NMR spectroscopy results showed that Pebax1657 exhibited the characteristic signal of NH protons in the polyamide segments at δ=7.74 ppm; while mPEG-OH showed the characteristic signal of -OCH3 protons in the terminal methoxy groups at δ=3.24 ppm. After end-group modification, the mPEG-modified Pebax1657 still retained the characteristic signal of NH protons in the polyamide segments at δ=7.72 ppm, indicating that the polyamide segment structure of Pebax1657 was preserved during the modification process.

[0035] Compared to Pebax1657, the mPEG-modified Pebax1657 exhibits a characteristic signal of a -OCH3 proton at the mPEG terminal group at δ=3.23 ppm, and a new methylene proton signal at δ=4.11 ppm. The signal at δ=4.11 ppm can be attributed to the -OCH2- proton adjacent to the carbonyl group in the carbonate linkage structure, indicating a change in the chemical environment of the mPEG terminal methylene group. The relative integral values ​​of the signals at δ=4.11 ppm and δ=3.23 ppm are approximately 1.77 and 3.00, respectively, close to the theoretical proton ratio of -OCH2- to -OCH3 at the mPEG terminal group in the carbonate linkage structure, which is 2:3.

[0036] The product obtained in Example 1 was subjected to hexane precipitation, repeated washing, and vacuum drying before NMR testing to reduce the influence of unreacted small molecules and residual impurities on the test results. The newly appearing methylene proton signal at δ=4.11 ppm, the terminal methoxy signal at δ=3.23 ppm, and the corresponding integral ratio together indicate that mPEG-OH is attached to the end of the Pebax1657 molecular chain via a CDI-mediated end-group coupling reaction.

[0037] Test Example 2 Infrared Spectroscopic Characterization Fourier transform infrared spectroscopy was performed on the Pebax1657 polymer, the mPEG-OH-10% modified Pebax polymer in Example 1, the mPEG-OH-20% modified Pebax polymer in Example 2, and the mPEG-OH-30% modified Pebax polymer in Example 3. The results are as follows: Figure 2 As shown.

[0038] like Figure 2 As shown, Pebax1657 and the modified samples obtained in Examples 1-3 all have a diameter of approximately 3300 cm. -1 An NH / OH-related absorption peak appears nearby, at approximately 2900 cm⁻¹. -1 A -CH2-related absorption peak appears nearby, at approximately 1630 cm⁻¹. -1 1540 cm -1 and 1100cm -1 The characteristic absorption peaks of amide groups and ether bonds in the Pebax1657 main structure are still present nearby, indicating that the main block structure of Pebax1657 still exists after end-group modification, and the modification process did not significantly damage its main chain structure. Meanwhile, compared with unmodified Pebax1657, the modified samples obtained in Examples 1-3 show enhanced characteristics in the polyether segment-related absorption regions, especially in the CO bond-related absorption region, indicating that mPEG-OH has been successfully introduced into the Pebax1657 system. With the increase of the mPEG-OH introduction ratio, the characteristic absorption of the relevant polyether segments gradually increases, indicating that the amount of polyether segments introduced into Pebax1657 varies with different modification degrees. The above results show that the method of CDI activation followed by the introduction of mPEG-OH in this invention can achieve end-group polyetherification modification while maintaining the main block structure of Pebax1657, and effectively improve the polyether segment characteristics in the material, providing a structural basis for subsequent regulation of polymer segment stacking and film formation behavior.

[0039] Test Example 3 XRD Characterization X-ray diffraction tests were performed on the Pebax1657 polymer, the mPEG-OH-10% modified Pebax polymer in Example 1, the mPEG-OH-20% modified Pebax polymer in Example 2, and the mPEG-OH-30% modified Pebax polymer in Example 3. The results are as follows: Figure 3 As shown.

[0040] like Figure 3 As shown, Pebax1657 and the modified samples obtained in Examples 1-3 all retained the characteristic diffraction peaks of polyether block polyamide materials, indicating that the basic crystal structure characteristics of Pebax1657 still exist, and the end-group modification did not destroy its main aggregated structure. Compared with unmodified Pebax1657, the characteristic diffraction peak shape, peak intensity, and relative width of the modified samples obtained in Examples 1-3 changed to some extent near approximately 20° and 23-24°, indicating that the end-group polyetherification modification affected the stacking mode and crystallization behavior of Pebax1657 molecular chains. Specifically, the characteristic diffraction peaks of the modified samples gradually changed from the original peak shape of Pebax1657 to a new peak shape distribution, indicating that the introduction of mPEG-OH changed the original inter-segment interactions and local ordered arrangement. As the proportion of mPEG-OH introduced further increased from Example 1 to Example 3, this trend became more obvious, indicating that the increase in the degree of modification would further affect the aggregated structure of Pebax1657. The results indicate that the end-group modification strategy employed in this invention is not a simple physical mixing, but rather a method that can regulate the segment stacking and crystallization behavior of Pebax1657 while maintaining its main structure.

[0041] The above results demonstrate that end-group polyetherification modification can effectively alter the microstructure of Pebax1657, providing favorable conditions for improving its casting solution state, film uniformity, and subsequent gas transport behavior.

[0042] Test Example 4: Characterization of membrane surface and cross-sectional morphology The Pebax 1657 thin film composite film prepared in Comparative Example 1 and the mPEG-Pebax thin film composite film prepared in Example 4 were tested by scanning electron microscopy. The results are as follows: Figure 4 As shown.

[0043] like Figure 4As shown, both the Pebax1657 film composite membrane prepared in Comparative Example 1 and the mPEG-Pebax film composite membrane prepared in Example 4 formed continuous film layers on their surfaces, indicating that both systems can form a selective separation layer on the support layer surface. However, compared with Comparative Example 1, the surface of the mPEG-Pebax film composite membrane obtained in Example 4 is more uniform and smooth, with fewer local bright spots and uneven areas. This indicates that after mPEG-OH end-group polyetherification modification, the uniformity of the casting solution and the film-forming behavior of Pebax1657 are improved, which is more conducive to forming a continuous and stable selective layer on the support layer surface. The cross-sectional morphology shows that the selective separation layer thickness of the Pebax1657 film composite membrane obtained in Comparative Example 1 is approximately 190 nm, while the selective separation layer thickness of the mPEG-Pebax film composite membrane obtained in Example 4 is approximately 130 nm. This indicates that under the same film-forming conditions, Pebax1657 modified with mPEG-OH end groups is more conducive to forming a thinner and more uniformly distributed selective separation layer. The results indicate that end-group polyetherification modification not only affects the molecular chain structure of Pebax1657, but also further affects its spreading behavior and dense layer construction process in thin film composites.

[0044] The combined surface and cross-sectional morphology results show that the end-group modification strategy adopted in this invention is beneficial to improving the film formation uniformity and structural integrity of the thin film composite membrane, and helps to construct a thinner selective separation layer, which is of positive significance for reducing mass transfer resistance and improving gas separation performance.

[0045] Test Example 5: Gas Separation Performance Test The membrane composite membranes prepared in Examples 4-6 and Comparative Examples 1-3 were tested for CO2 / N2 mixed gas separation performance, and the results are shown in Table 1. During the test, the membrane samples were sealed in a membrane cell. A CO2 / N2 mixed gas was introduced into the feed gas side, and He was used as the purge gas on the permeate side at atmospheric pressure. The gas composition on the permeate and feed sides was analyzed by gas chromatography. The permeation rate (in GPU) of each gas component was calculated based on the effective membrane area, gas flow rate, and gas composition. The separation factor of the two gases was the ratio of the corresponding gas permeation rates.

[0046] Permeation rate ( R The definition of ) is shown in equation (1-1): (1-1) In the above formula, R i Components i The permeation rate of the separation membrane is expressed in GPUs (1 GPU = 10^10). -6 cm 3 (STP) cm - 2 s-1 cmHg -1 = 3.35×10 -10 mol m -2 s -1 Pa -1 ); Q i Components i The volumetric flow rate through the gas separation membrane at standard temperature and pressure, expressed in cm. 3 (STP) / s; P i It is a component i The partial pressure difference across the gas separation membrane, expressed in cmHg; A Effective membrane area, in cm² 2 .

[0047] Meanwhile, the selectivity of the separation membrane is usually measured by the separation factor ( The separation factor reflects the rate at which different components pass through the separation membrane. i and j The ratio of permeability coefficients ( ) or permeation rate ratio ( The ideal separation factor is defined as shown in equation (1-2): (1-2).

[0048] Table 1. Test results of CO2 / N2 mixed gas separation performance of the thin film composite membranes prepared in Examples 4-6 and Comparative Examples 1-3 As shown in Table 1, the CO2 / N2 separation performance of the Pebax1657 membrane composite was significantly improved after mPEG-OH end-group polyetherification modification. Compared with the unmodified Pebax1657 membrane composite, the modified membrane exhibited higher overall CO2 / N2 selectivity, indicating that end-group modification can effectively improve the separation capability of the membrane material. Furthermore, as the proportion of mPEG-OH introduced increased from 10% to 30%, the CO2 permeability of the membrane composite gradually decreased, while the CO2 / N2 selectivity gradually increased, indicating that end-group polyetherification modification affected the molecular chain stacking mode and membrane microstructure of Pebax1657. With increasing modification degree, the sieving capacity of the membrane layer is enhanced, which is beneficial to improving CO2 / N2 selectivity, but it also reduces the CO2 transport rate to some extent.

[0049] Furthermore, the results of Comparative Examples 2 and 3 indicate that simply blending mPEG-OH or CDI directly with Pebax1657 does not achieve the same effect as end-group polyetherification modification. In particular, while the CDI / Pebax1657 film composite membrane exhibits high CO2 permeability, its CO2 / N2 selectivity is significantly lower, demonstrating that simple blending cannot simultaneously achieve both gas transport capacity and separation selectivity.

[0050] In summary, the end-group polyetherification modification strategy employed in this invention can effectively regulate the membrane structure of Pebax1657 and improve its CO2 / N2 separation performance. Furthermore, different modification ratios can achieve adjustment of gas permeability and selectivity, providing a basis for subsequent optimization of membrane performance according to application requirements.

Claims

1. A gas separation composite membrane for mPEG-OH modified polyether block polyamide, characterized in that, The invention includes a base film and a selective separation layer disposed above the base film; the selective separation layer is formed of mPEG-OH modified polyether block polyamide; the mPEG-OH modified polyether block polyamide utilizes carbonyl diimidazole as a coupling agent to activate the terminal hydroxyl groups of the polyether block polyamide, and then covalently couples it with the terminal hydroxyl groups of mPEG-OH to form a modified polymer with an extended main chain structure.

2. The composite membrane according to claim 1, characterized in that, The base film is a porous support layer or a porous support layer including an intermediate layer; the intermediate layer is a polydimethylsiloxane layer; the porous support layer is one of polysulfone, polyethersulfone, polyacrylonitrile, polyvinylidene fluoride, polytetrafluoroethylene, polypropylene, polyethylene, polyimide, polyetherimide, or polyphenylene sulfide.

3. The composite membrane according to claim 1, characterized in that, The flexible segment of the polyether block polyamide is polyethylene oxide; and / or, the polyether block polyamide is polyether block polyamide 1657; and / or, the weight-average molecular weight of the mPEG-OH is 500 to 10,000 Daltons.

4. A method for preparing a composite membrane as described in any one of claims 1-3, characterized in that, Includes the following steps: Step 1: Dissolve the polyether block polyamide in a mixed solvent and stir under heating until dissolved to obtain a polymer solution; Step 2: Add carbonyl diimidazole to the polymer solution obtained in Step 1 to activate the terminal groups of the polyether block polyamide molecular chain. Step 3: Add mPEG-OH to the system obtained in Step 2 and continue the reaction to obtain mPEG-OH modified polyether block polyamide; Step four: The product obtained in step three is prepared into a casting solution, and the casting solution is coated on the surface of the base film. After drying, a selective separation layer is formed, thereby obtaining the composite film.

5. The method according to claim 4, characterized in that, In step one, the mixed solvent is a mixture of ethanol and water, with a mass ratio of ethanol to water of 10-90:90-10; and / or, in step one, the heating condition is stirring at 40-120°C.

6. The method according to claim 4, characterized in that, In step two, the reaction temperature is 10-100℃ and the reaction time is 0.1-10 hours; and / or, in step three, the reaction temperature is 20-80℃ and the reaction time is 0.1-10 hours.

7. The method according to claim 4, characterized in that, The mass ratio of the polyether block polyamide, carbonyl diimidazole and mPEG-OH is 100:5-80:5-80.

8. The method according to claim 4, characterized in that, After step three, a purification step is also included: the reaction solution is poured into excess n-hexane for precipitation, the precipitated product is separated and / or washed, and then vacuum dried at 30-100℃ for 1-100 hours to constant weight to obtain purified mPEG-OH modified polyether block polyamide; and / or, in step four, coating is performed by blade coating and / or spin coating.

9. The application of the composite membrane according to any one of claims 1 to 3 in the field of mixed gas separation.

10. The application according to claim 9, characterized in that, The mixed gas comprises carbon dioxide and at least one of the group consisting of nitrogen, methane, hydrogen and carbon monoxide, wherein the carbon dioxide permeates through the composite membrane.

Citation Information

Patent Citations

  • Gas separation membrane comprising crosslinked blends of rubbery polymers

    US20210162355A1